Relationship between CRP of COVID-19 Patients with Severity and Outcome - Suyoso, -; Rachmawaty, Farida Juliantina; Prabowo, Bagastyo Afif (International Journal of Human and Health Sciences (IJHHS), 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Serum C-Reactive Protein (CRP) is an important marker that is significantly significant in the severity of COVID-19 patient outcomes. An increase in CRP indicates an increased risk of disease progression. IL-6 levels will also increase to become a strong predictor of the risk of damage to the respiratory system. This study aims to determine the relationship between CRP of COVID-19 patients with severity and outcome. This study is an observational study with a cross-sectional design. The subjects involved in the study were COVID-19 patients at the dr. Soedono Madiun in the period January 2020 - April 2021. The instrument used is secondary data in medical records from RSUD dr. Soedono Madiun. There was no significant difference in CRP levels in 114 patients hospitalized for <12 days and >12 days (p=0.051), then the duration of hospitalization was also not correlated with CRP levels (p=0.70, r =-0.251). In addition, there was a significant difference in CRP levels between patients with severe and non-severe severity (p=0.0013). The patient’s severity was also positively correlated with CRP level (p=0.012, r=0.233). There was a significant difference in CRP levels in patients with recovered and dead outcomes and was positively correlated (p=0.000, r=0.378). CRP levels are related to the severity and outcome of COVID-19 patients. A high CRP indicates severity and risk of death. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 452-456